ЭЛЕКТРОН ЎҚУВ АДАБИЁТЛАРИ ЯРАТИШНИНГ МЕТОДИК ТАМОЙИЛЛАРИ (“Материаллар қаршилиги” фани мисолида) - Эшбаева, З.Н. (SCIENCE and SOCIETY, 2022)
The article defines the concept of an electronic textbook in a new edition and classifies the methodological principle of independent action and activity for the creation of electronic textbooks for technical education, the components of which are scientifically substantiated in form and content.
Keywords: electronic textbook; didactics; methodological principles; multimedia; motivation; distance learning; independent learning